2020
DOI: 10.1111/pbr.12827
|View full text |Cite
|
Sign up to set email alerts
|

Using public databases for genomic prediction of tropical maize lines

Abstract: In this paper, the aims were (a) to test the usefulness of using genomic and phenotypic information from public databases (open access) to predict genetic values for tropical maize inbred lines regarding plant and ear height; (b) to identify how the population structure, the use of optimized training sets (OTSs) and the amount of information originating from public databases affect the predictive ability. Thus, 29 training sets (TSs) were defined considering three diversity panels: the University of São Paulo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
5
10
0
Order By: Relevance
“…Moreover, the samples have a good distribution of genotypes, including those genotypes that perform well, and those that are not so good, bringing positive impacts on PA (Michel et al, 2020). As expected and similar to what Pinho Morais et al (2020) found, with a small effective population size, PA is diminished, since the sample contains small genetic variability.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, the samples have a good distribution of genotypes, including those genotypes that perform well, and those that are not so good, bringing positive impacts on PA (Michel et al, 2020). As expected and similar to what Pinho Morais et al (2020) found, with a small effective population size, PA is diminished, since the sample contains small genetic variability.…”
Section: Discussionsupporting
confidence: 76%
“…The establishment of the TRN, which should be representative in terms of size, diversity, and the relationship of the individuals to be predicted, is the key to success in GS (Jannink et al, 2010;Akdemir et al, 2015;Crossa et al, 2017;Varshney, 2017;Ibba et al, 2020). For that, the main objectives are to minimize costs associated with phenotyping by selecting smaller training populations, and maximize the predictive ability for the individuals of the TST through efficient resource allocation (Isidro et al, 2015;Lado et al, 2018;Pinho Morais et al, 2020;Riedelsheimer & Melchinger, 2013;Technow et al, 2014). Additionally, there is a lack of knowledge on how to distribute genotypes optimally in multi-environment trials in order to achieve the best balance between the number of genotypes tested in the field and the predictive capacity of GP models, and maximize the selection gain with fixed area and budget resources (Jarquin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the scarcity of resources in the initial phases, we addressed the possibility of incorporating public databases in the composition of our training populations (Morais et al, 2020). Small-scale public and private programs with limited budgets often lack the financial ability to genotyping a considerable number of individuals to apply GP efficiently.…”
Section: Training Populations Using Public Databases-an Alternativementioning
confidence: 99%
“…Small-scale public and private programs with limited budgets often lack the financial ability to genotyping a considerable number of individuals to apply GP efficiently. In this regard, Morais et al (2020) These databases contained phenotypic information regarding plant height (PH, in cm), ear height (EH, in cm), and the SNP markers data. A total of 29 training populations (TPs) were defined and divided into four scenarios to determine the best strategy to apply public databases to predict lines.…”
Section: Training Populations Using Public Databases-an Alternativementioning
confidence: 99%